2021
DOI: 10.1007/s10994-021-06042-2
|View full text |Cite
|
Sign up to set email alerts
|

Special issue on feature engineering editorial

Abstract: In order to improve the performance of any machine learning model, it is important to focus more on the data itself instead of continuously developing new algorithms. This is exactly the aim of feature engineering. It can be defined as the clever engineering of data hereby exploiting the intrinsic bias of the machine learning technique to our benefit, ideally both in terms of accuracy and interpretability at the same time. Often times it will be applied in combination with simple machine learning techniques su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…We defined a feature set in the time-domain, frequencydomain, as well as time-frequency domain (these are waveletrelated variables) in a process called feature engineering (Verdonck et al, 2021). In addition to standard statistical features, we used number and energy content of EDA events and storms, as they are known to differ for different sleep stages (Sano et al, 2014) and OSA severity (Arnardottir et al, 2010).…”
Section: Feature Extraction and Selectionmentioning
confidence: 99%
“…We defined a feature set in the time-domain, frequencydomain, as well as time-frequency domain (these are waveletrelated variables) in a process called feature engineering (Verdonck et al, 2021). In addition to standard statistical features, we used number and energy content of EDA events and storms, as they are known to differ for different sleep stages (Sano et al, 2014) and OSA severity (Arnardottir et al, 2010).…”
Section: Feature Extraction and Selectionmentioning
confidence: 99%
“…In other contexts, such as materials informatics and natural language processing, it has been shown that the quality of the encoding is critical to the performance of machine learning models. [74][75][76][77][78] Here, we focus on three methods of featurization: sequence vectors, token counting, and implicit feature learning.…”
Section: Supervised Learningmentioning
confidence: 99%
“…From a machine learning perspective, all used explanatory variables represent "handcrafted" features whose selection is based on domain or expert knowledge [85]. This mainly concerns the determination of multi-scale tuning parameters (cf., Table 1) and scale levels (see Section 2.1.4).…”
Section: Scale-specific Optimizationmentioning
confidence: 99%